1997
DOI: 10.1093/bja/79.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of controlled release morphine (MST) in patients with liver cirrhosis

Abstract: We have studied the kinetic profile of controlled release morphine (MST) in 12 patients with posthepatitic cirrhosis, caused by HCV and HBsAg, with portal hypertension, given MST 30 mg for endoscopic sclerotherapy and compared the data with those from 10 healthy controls. Plasma drug concentrations were measured in venous blood samples at intervals up to 12 h by high-pressure liquid chromatography (HPLC). Total body clearance (Cl) and systemic availability were estimated using a compartmental method. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The role of oxymorphone in the total analgesic effect of oxycodone is, however, not yet clear. Liver dysfunction affects the metabolism of both oxycodone and morphine by increasing the elimination halflife and reducing plasma clearance (25,26). In kidney failure, oxycodone elimination is prolonged because of increased volume of distribution and reduced clearance (27).…”
Section: Discussionmentioning
confidence: 99%
“…The role of oxymorphone in the total analgesic effect of oxycodone is, however, not yet clear. Liver dysfunction affects the metabolism of both oxycodone and morphine by increasing the elimination halflife and reducing plasma clearance (25,26). In kidney failure, oxycodone elimination is prolonged because of increased volume of distribution and reduced clearance (27).…”
Section: Discussionmentioning
confidence: 99%
“…Derived kinetic variables in control healthy volunteers have been published and fitted closely to other reported data. 6 Patients with liver cancer showed a 3-4-fold increase in the peak concentration of morphine presumably as a result of the reduction in first pass metabolism secondary to a reduction in liver cell mass; this led to an increase in total systemic Table 1 The pharmacokinetic values of oral MST 30 mg tablets in the control, primary and secondary liver cancer patients. a,b Significant difference (P<0.05) with the control and between the two cancer groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They all had normal renal and liver function with negative tests for hepatitis. 6 Administration of morphine was started at 10:00 in all patients. A cannula was inserted into an antecubital vein under local anaesthesia to facilitate sampling of venous blood.…”
Section: Study Protocolmentioning
confidence: 99%
“…10 More recent studies have found a decreased plasma clearance and prolonged elimination half-life in patients with cirrhosis, compared to control patients without liver disease, therefore necessitating a reduction in dosage. 11,12 Pharmacokinetics of controlled release morphine in normal subjects and cirrhotic patients have been studied by Kotb et al, 13 and they found that the elimination half-life and total body clearance were significantly altered in the latter group. This suggests that accumulation is more likely to occur in patients with liver failure, with increased risk of opioid toxicity and the recommendations have been to decrease frequency of administration.…”
Section: Opioid Analgesiamentioning
confidence: 99%